Face-to-Face Clinical Practice Under COVID-19 Pandemic: How Psychotherapists Describe Their Experiences - Ribeiro, Eugénia; Ferreira, Ângela; Cardoso, Cátia; Queiroz, Raquel; Silva, Vânia (Frontiers in Psychology, 2021)
Driven by the theory-building around the role of the nonverbal components to communication, we aimed to understand how therapists experience the therapeutic process using a facial mask. The empirical evidence of the power of nonverbal communication to engage therapists and clients in therapeutic work, develop a positive and collaborative relationship between them, and display empathy is quite large. A mixed-methods approach was adopted, drawing from the therapists' participation in an online survey. A sample of 137 psychotherapists with different therapy orientations and years of clinical practice participated in the study. Therapists conducted face-to-face therapy wearing face masks with existing and/or new clients. We performed an exploratory analysis, using descriptive statistics, to explore the psychotherapists' evaluations regarding the perceived impact of face masks on different therapy quality dimensions. In a complementary rationale, we analyzed the therapists' perspectives on their experience wearing face masks using the thematic analysis methodology. Results show that among 137 psychotherapists, 114 were attending both existing and new clients, whereas only 13 were seeing exclusively existing clients and 10 were working exclusively with new clients. Despite no major differences were found between conditions regarding the perceived impact of face masks on different therapy quality dimensions and strategies adopted, the qualitative analysis allowed us to expand the quantitative results and deepen our understanding of psychotherapists’ experience. Based on general and typical patterns, we propose two distinct models to describe the therapist's experiences narrative when working with existing or new clients wearing face masks. Based on the results, we propose some recommendations to clinical practice in similar conditions.